Interaction of bending and axial load for ferritic stainless steel RHS columns. (June 2015) - Arrayago, I.; Picci, F.; Mirambell, E.; Real, E.
Abstract: Stainless steels are ideal for sustainable structural performances due to their excellent corrosion resistance, appropriate mechanical properties, aesthetic appearance and easy maintenance. However, the nonlinear behaviour and strain-hardening effects characterizing these materials make them different from carbon steel and some specific guidance is necessary. Although some investigations regarding the behaviour of stainless steel beam–columns subjected to combined compression and bending moment have already been published, most of them are based on the most commonly used austenitic and duplex grades. Hence, the work presented in this paper deals with the flexural buckling resistance of ferritic stainless steel RHS and SHS columns subjected to combined loading. The assessment of several design approaches codified in EN1993-1-4 and proposed in the literature has been conducted by comparing numerical results with the predicted ultimate capacities. The partial safety factor γ M 1 currently coded in EN1993-1-4 has been found to provide unsafe ultimate flexural buckling resistance predictions and new coefficients for the k interaction factor for ferritic RHS and SHS elements are proposed. Highlights: The behaviour of ferritic stainless steel beam–columns is investigated. FE results considering different bending moment diagrams are presented. The assessment of design approaches for flexural buckling resistance is presented. Interaction expressions for combined loading in beam–columns are assessed.